2011
DOI: 10.1016/j.jss.2010.11.882
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Iliac Rat Aorta Stenting: A Novel High Throughput Preclinical Stent Model for Restenosis and Thrombosis

Abstract: Background-Currently, preclinical stent development requires elaborate large animal models which are time consuming and expensive. We herein report a high throughput rat aorta stenting model which could provide a rapid and low-cost platform for preclinical stent development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…AAo stenting was performed under anesthesia and sterile conditions (12,36). Local BF patterns and the subsequent severity of NH are influenced by stent geometry (29).…”
Section: Methodsmentioning
confidence: 99%
“…AAo stenting was performed under anesthesia and sterile conditions (12,36). Local BF patterns and the subsequent severity of NH are influenced by stent geometry (29).…”
Section: Methodsmentioning
confidence: 99%
“…The small peripheral vasculature diameter of a medium sized rat makes trans-carotid and trans-iliac endovascular device deployment difficult 5,6 . However, devices can also be placed through direct abdominal aortic insertion or direct placement into the experimental aneurysm before end-tosite anastomosis 7,16 .…”
Section: Discussionmentioning
confidence: 99%
“…Murine aneurysm models, on the other hand, allow testing research questions in genetically modified species 3,4 and facilitate clarification of aneurysm biology at cellular and molecular level far better than larger species 1 . Although endovascular trans-carotid and trans-iliac device deployment is limited to bigger rats (>400-500 g) and stents smaller than 2.0 mm and 1.5 mm in diameter 5,6 , stents can also be placed through direct insertion into the abdominal aortic segment harbouring the experimental aneurysms. Previous work using the rat microsurgical abdominal aortic sidewall aneurysm model demonstrated its feasibility in testing novel embolic devices and its use in studying the molecular basis of aneurysm biology 3,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown high rates of mortality in abdominal stent implantation. The values vary from 5.7 -57% 12,13,14,15 . Most animals died of thrombosis following the intima injury during stent implantation 16 .…”
Section: Morbidity and Mortalitymentioning
confidence: 99%